1926
DOI: 10.1001/archpedi.1926.04130090050007
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis Therapy in Cardiac Decompensation in Children

Abstract: Digitalis is often believed to be ineffectual in the treatment of cardiac disease in children. The most probable explanation for this belief is that the doses commonly used have been too small, for McCulloch and Rupe 1 have demonstrated that both normal children and those suffering from heart disease require from 10 to 100 per cent more digitalis per pound of body weight than do adults before electrocardiographic or other signs of digitalization are produced. Our studies of twenty-six children suffering from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1928
1928
1952
1952

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The number of its functions which influence the effect of digitalis must be great. It has been shown that age is important, for young children require up to two or two and a half times the body-weight dose for adults (5). The Eggleston method (3) of giving the drug has been found very useful, and has done much to clarify the problems of the clinical use of digitalis.…”
mentioning
confidence: 99%
“…The number of its functions which influence the effect of digitalis must be great. It has been shown that age is important, for young children require up to two or two and a half times the body-weight dose for adults (5). The Eggleston method (3) of giving the drug has been found very useful, and has done much to clarify the problems of the clinical use of digitalis.…”
mentioning
confidence: 99%